Current European Labyrinthula zosterae are not virulent and modulate seagrass (Zostera marina) defense gene expression. - Janina Brakel (Public Library of Science (PLoS), 2014)
Pro- and eukaryotic microbes associated with multi-cellular organisms are receiving increasing attention as a driving factor in ecosystems. Endophytes in plants can change host performance by altering nutrient uptake, secondary metabolite production or defense mechanisms. Recent studies detected widespread prevalence of Labyrinthula zosterae in European Zostera marina meadows, a protist that allegedly caused a massive amphi-Atlantic seagrass die-off event in the 1930's, while showing only limited virulence today. As a limiting factor for pathogenicity, we investigated genotype × genotype interactions of host and pathogen from different regions (10-100 km-scale) through reciprocal infection. Although the endophyte rapidly infected Z. marina, we found little evidence that Z. marina was negatively impacted by L. zosterae. Instead Z. marina showed enhanced leaf growth and kept endophyte abundance low. Moreover, we found almost no interaction of protist × eelgrass-origin on different parameters of L. zosterae virulence/Z. marina performance, and also no increase in mortality after experimental infection. In a target gene approach, we identified a significant down-regulation in the expression of 6/11 genes from the defense cascade of Z. marina after real-time quantitative PCR, revealing strong immune modulation of the host's defense by a potential parasite for the first time in a marine plant. Nevertheless, one gene involved in phenol synthesis was strongly up-regulated, indicating that Z. marina plants were probably able to control the level of infection. There was no change in expression in a general stress indicator gene (HSP70). Mean L. zosterae abundances decreased below 10% after 16 days of experimental runtime. We conclude that under non-stress conditions L. zosterae infection in the study region is not associated with substantial virulence.